Panduan Guru Penelitian Tindakan Kelas. A Teacher's Guide to Classroom Research - HOPKINS, David (Pustaka Pelajar, 2011)
Panduan Guru Penelitian Tindakan Kelas. A Teacher's Guide to Classroom Research